2013
DOI: 10.1177/1363460713508903
|View full text |Cite
|
Sign up to set email alerts
|

Consensual non-consent: Comparing EL James’s Fifty Shades of Grey and Pauline Réage’s Story of O

Abstract: This article explores questions of sexual agency and consent in mainstream representations of BDSM using Pauline Réage's Story of O and EL James's Fifty Shades trilogy as examples. It addresses normalizing tendencies and explores to what extent BDSM can be represented before being rejected by mainstream readers. Based on critiques of both novels, I outline the degree to which the concept of consensual non-consent, that is, the illusion of suspended consent in order to facilitate erotic power play, works in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Fifty Shades of Grey [10] is a series of erotic novels that gained massive sales figures in recent years and has brought awareness of BDSM practices to a large audience [2]. Of relevance to the current paper, apart from their erotic content, these novels are remarkable for the controlling nature of the relationship between it's main characters (see [2][6] [21]). Thus, as a recent cultural phenomenon that features centrally an unhealthy and controlling relationship, we felt that Fifty Shades of Grey provided the perfect vehicle for our metaphor.…”
Section: Discussionmentioning
confidence: 98%
“…Fifty Shades of Grey [10] is a series of erotic novels that gained massive sales figures in recent years and has brought awareness of BDSM practices to a large audience [2]. Of relevance to the current paper, apart from their erotic content, these novels are remarkable for the controlling nature of the relationship between it's main characters (see [2][6] [21]). Thus, as a recent cultural phenomenon that features centrally an unhealthy and controlling relationship, we felt that Fifty Shades of Grey provided the perfect vehicle for our metaphor.…”
Section: Discussionmentioning
confidence: 98%
“…It includes work on searching for sexual partners, use of internet as a method of solicitation and advertisement of sex-work; cybersex; issues of addiction, gender variances; discourses of consumerism, therapy, the expression of self-identity and creation of communities within sexuality; sexualized fanfiction and fan-art; use of internet for queer or sexually subcultural identity-construction, sexting, fidelity, etc. (see Albright, 2008;Attwood, 2010;Binik, 2001;Brand et al, 2011;Burr, 2003;Castle & Lee, 2008;Chaline, 2010;Cooper, Månsson, Daneback, Tikkanen, & Ross, 2003;Daneback, Cooper, & Mansson, 2005;Daneback, Månsson, & Ross, 2007;Daneback, 2006;Döring, 2009;Griffiths, 2001;Ferree, 2003;Hasinoff, 2012;Keft-Kennedy, 2005;Lehman, 2007;Leiblum, 2001;Ross, Rosser, McCurdy, & Feldman, 2007;Sevickova & Daneback, 2011;Tsaros, 2013;Weiss & Samenow, 2010;Weisskirch & Delevi, 2011;Whitty, 2008;). In other words, internet has transfigured sex and sexuality, creating new or illuminating other aspects of it so that they 'stand out from their equivalent social sexual interactions' (Ross, 2005, p. 342).…”
Section: Theoretical Context (Sexual) Self-expression Onlinementioning
confidence: 99%
“…One of Jamison's informants in the Twific community observed that this familiar structure allowed for sexual experimentation in the creative sandbox: “The sex is a given, the basic structure is a given, but the way the author takes you there–that's the variation and that variation provides the tension, but in a safe environment–readers know the outcome and the relationships.” The roots of 50 Shades of Grey in vampire texts make the stalking less surprisingly new, given that vampires stalk their victims in their bedrooms at night with sensual violence in mind. The seeming daringness of 50 Shades of Grey is not very daring at all in this intertextuality, according to some feminist critics who have pointed out the confirmation of heterosexual monogamy and the dequeering of Christian Grey in the familiar structure of the long plot (Mahadin; Tsaros).…”
mentioning
confidence: 99%